I still dream about you : a novel - Flagg, Fannie (Random House, 2010)
Birmingham real estate agent and former Miss Alabama Maggie Fortenberry learns valuable lessons about the nature of friendship, the challenges of modern life, and the dangers of impossible dreams as she struggles to keep Red Mountain Realty afloat and bury the heartbreaking secrets of her past.